الذكاء الوجداني وعلاقته بالثقة بالنفس لدى طلاب كلية التربية قسم التربية الرياضية-جامعة الحمدانية - مجيد, سعود عبدالغني (Sulaimani Journal for Humanities, 2018)
Summary Aim of the study: The present study aimed at detecting the nature of the relationship between emotional intelligence and self-confidence and detect differences in emotional intelligence and self-confidence among students of the college of physical education. Hamdania university in light of some of the variables (sex-type hits practice). The research sample: the research sample consisted of (120)male and female students and religion represent the student of the college of physical education ,all for the academic year2016-2017.(80)males and (40)females. Tools of the study: The researcher used the emotional intelligence scale of preparation Ahmed Alwan and the measure of self-confidence by Qawasm and Farh (1996). Statistical methods used:Statistical have been using data processing program (Spss) it allowed the application of the following statistical tools (Pearson correlation ,coefficient,T-test differences ,duplicates ,percentage ,arithmetic mean ,standard deviation. Results of the study: 1-there is a significant statistical correlation between emotional intelligence and self-confidence among studyents of the college of education university. 2-no statistically significant diffefences between the males and females in emotional intelligence in favor of variable females.3-no statistically significant differences between males and females in self-confidence for the male variant. Recommendations : directing the authors of curricula and programs in the Ministry of Higher education and scientific research to the importance of emotional intelligence in the acquisition of university students basic life skills that contribute to the achievement success.